TheArcheological site of Los Hitos in Arisgotas (Orgaz-Toledo). - Moreno Martín, Francisco J. (Anales de Historia del Arte, 2008)
This archaeological deposit was considered as a monastic establishment of the Visigothic period by the historiography. The weak arguments used in that sense take us to think about the way to identify those monasteries built between the Late Antique and the Early Middle Ages. Along this article we will try to examine the relationships between those arguments andthe recent periodlivedby our historiography around the research of the Visigothic art and architecture. After our study we are ready to enunciate the doubts about the identification of this archaeological place as a cenobitic complex.